Application of the Gadidae Fish Processing Waste for Food Grade Gelatin Production - Nikita Yu. Zarubin; Elena N. Kharenko; Olga V. Bredikhina; Leonid O. Arkhipov; Konstantin V. Zolotarev; Anton N. Mikhailov; Valeriya I. Nakhod; Marina V. Mikhailova (Marine Drugs, 2021)
Waste from fish cutting (heads, swim bladders, fins, skin, and bones) is a high-value technological raw material for obtaining substances and products with a wide range of properties. The possibility of using waste from cutting fish of the Gadidae family: the Alaska pollock (Gadus chalcogrammus) and the Pacific cod (Gadus macrocephalus), processed in the coastal zone, is scientifically substantiated. In this work, a technology has been developed for processing accumulated waste from fish cutting in order to obtain fish gelatin, which is characterized by high protein content (more than 80.0%) and a full set of essential and nonessential amino acids. We studied the quality of fish gelatin obtained from wastes from cutting the fish of the Gadidae family. The possibility of using fish gelatin as a component of fish products is shown; the dose of its introduction into the fish products is substantiated. The data obtained made it possible to recommend the use of fish processing waste products as a gelling component and a source of amino acids in multicomponent food systems.